Influence of microfluidization on physico-chemical, rheological, thermal properties and cholesterol level of cow ghee. (15th April 2022) - Dhiman, Atul; Suhag, Rajat; Verma, Kiran; Thakur, Dhruv; Kumar, Anit; Upadhyay, Ashutosh; Singh, Anurag
Abstract: Application of microfluidization can influence physicochemical, structural, rheological and functional properties of the food matrix, significantly. In the present research, effect of high pressure microfluidization treatment (50–200 MPa, single pass) on pH, refractive index (RI), free fatty acid (FFA) values, colour measurements, rheology, particle size, structural properties and thermal properties of cow ghee (CG) were investigated. Upon microfluidization, the pH values of CG significantly increased from 4.5 to 4.9. The shear-thinning nature of microfluidized CG was demonstrated by a Rheogram between apparent viscosity and shear rate. At 50 MPa, the apparent viscosity of the sample increased but then decreased as the microfluidization pressure was increased. Thermal analysis revealed an increase in glass transition temperature (Tg ) at 50 MPa from 32 to 37 °C and a significant effect was observed on it as the pressure was increased. GC-MS analysis revealed that microfluidization at 150 MPa reduced the cholesterol level in CG by 39.37%. The current research is the first one on microfluidization of CG and can open new channels on the research end. Graphical abstract: Image 1 Highlights: Cow ghee was microfluidized at different pressure (50–200 MPa) using single pass. Y type chamber preserved the quality parameters, FFA, colour and RI. Microfluidization increased the Tg showing highest at 50 MPa. Microfluidized cow ghee had shown shear thinning rheology. Highest increase in apparent viscosity was observed at 50 MPa.